2016
DOI: 10.1177/1070496516658753
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Framework for Integrated Economic–Environmental Modeling

Abstract: Economy-wide models such as computable general equilibrium (CGE) models are powerful tools that provide insights on policy impacts on standard economic indicators. With the recent publication of the System of Environmental-Economic Accounting (SEEA), the power of this approach is amplified. This article addresses an important gap in economy-wide policy modeling applications and literature by developing a conceptual framework for the integration of the SEEA in the CGE framework, enabling for the first time the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 39 publications
0
56
0
1
Order By: Relevance
“…A CGE approach has not been widely applied to exploring fisheries, though it has been shown that there is significant potential for extending a standard CGE framework to take into account fish population and management dynamics (Banerjee et al, 2016). The approach developed in this module follows guidance from the literature related to the integrated ecosystem-based -11-management of fisheries, which considers the entire ecosystem, including humans (Pikitch et al, 2004).…”
Section: The Ieem Platformmentioning
confidence: 99%
See 4 more Smart Citations
“…A CGE approach has not been widely applied to exploring fisheries, though it has been shown that there is significant potential for extending a standard CGE framework to take into account fish population and management dynamics (Banerjee et al, 2016). The approach developed in this module follows guidance from the literature related to the integrated ecosystem-based -11-management of fisheries, which considers the entire ecosystem, including humans (Pikitch et al, 2004).…”
Section: The Ieem Platformmentioning
confidence: 99%
“…One of the most useful features of the SEEA is the ability to combine in single framework physical and monetary quantities. Banerjee et al (2016) describe in detail the main elements of the SEEA which are relevant for integrated economic-environmental modelling.…”
Section: The Seea and The Ieem Databasementioning
confidence: 99%
See 3 more Smart Citations